The prevalence of preterm and low birth weight infants among migrant women in the Pearl River Delta region, China: a population-based birth cohort study - Lulu Xie; Zhijiang Liang; Xionghu Wang; Xianqiong Luo (BMC, 2024)
Abstract Background The existing literature evaluating the association between neonatal morbidity and migrant status presents contradictory results. The purpose of this study was to compare the risk of preterm birth (PTB) and low birth weight (LBW) among newborns from local and migrant women in China's Pearl River Delta (PRD) region. Methods In this observational population-based study, we included all live singleton deliveries from PRD region local women and migrant women. Data were sourced from the Guangdong Medical Birth Registry Information System between Jan 1, 2014, and Dec 31, 2020. Women were categorized into three groups by maternal migrant status: local women from PRD region, migrant women from Guangdong province or from other provinces. The outcome variables that were examined included two adverse birth outcomes: PTB and LBW. The association between the risk of PTB and LBW and maternal migrant status was assessed using logistic regression. Results During 2014-2020, 5,219,133 single live deliveries were recorded, corresponding 13.22% to local women and the rest to migrant women coming from Guangdong (53.51%) and other provinces (33.26%). PTB prevalence was highest among local women (5.79%), followed by migrant women from Guangdong (5.29%), and the lowest among migrants from other provinces (4.95%). This association did not change after including maternal age, infant sex, delivery mode, and birth season in the models. Compared to local women, migrant women from other provinces had a lower risk of LBW (4.00% vs. 4.98%, P < 0.001). The prevalence of PTB and LBW was higher among local women than migrants. The odds of delivery PTB and LBW were higher for women who were age ≥ 35. Among the three maternal migration groups, the age-LBW association displayed a typical U-shaped pattern, with those in the youngest (16-24 years) and oldest (≥ 35) age categories exhibiting the higher odds of delivering a LBW neonate. With respect to infant sex, the prevalence of PTB was significantly higher in males than females among the three maternal migration groups. An opposite trend was found for LBW, and the prevalence of LBW was higher in females among the three maternal migration groups. Conclusion The findings of this study contribute to the understanding of the epidemiology of PTB and LBW among migrant women. Our study suggests that it is the health and robust nature of migrant mothers that predisposes them to better birth outcomes. It is important to recognize that the results of this study, while supportive of the healthy migrant effect, cannot be considered definitive without some exploration of motivation for moving and changes in lifestyle postmigration.